Analysis Of Internal Control Systems On Merchandise Inventory Procedures At Perum Bulog Regional Office Of North Sulawesi - Wisnu Saputra Wagiu; Heidy Pesik; Jerry Lintong (Green Publisher Indonesia, 2024)
Inventory is very important in supporting the company's operational activities. Large quantities of inventory are vulnerable to the risk of damage, theft and misappropriation. Therefore, the internal control system must be implemented properly and effectively so that the inventory of goods is maintained. The purpose of this study is to determine the internal control carried out by Perum Bulog Kanwil North Sulawesi in order to get a clear picture of whether the internal control of inventory applied is effective. The method used in this study is a qualitative descriptive method, namely by conducting direct interviews with company employees. The results of research at Perum Bulog Kanwil North Sulawesi on internal control of inventory have been quite effective. Where there is a separation between functions related to receiving and dispensing inventory and all transaction activities and procedures already using system applications. However, Perum Bulog needs to pay attention to manual recording in anticipation of system damage that may occur.